Determinants of net interest margin in Nepalese commercial banks - Khadka, Srijana; Khadka, Ajaya (NCC Journal, 2020)
This study explored and analyzed the determinants of Net Interest Margin (NIM) of Nepalese commercial banks. The research focuses on three independent variables: Capital Adequacy Ratio (CAR), Credit-Deposit Ratio (CDR), and Non-Performing Loan Ratio (NPLR). Descriptive analysis and regression tests were conducted to analyze the data obtained from a sample of 10 commercial banks with 50 observations. The descriptive statistics reveal the mean and range of the variables, indicating the average and variability of CAR, CDR, NPLR, and NIM in the sample. The regression analysis examines the relationship between the independent variables and NIM. The findings suggest that CDR significantly impacts NIM, indicating that higher utilization of deposits for lending activities contributes to increased interest income and, ultimately, higher NIM. However, CAR and NPLR do not show significant relationships with NIM. The results of this study are consistent with previous research that emphasizes the importance of managing the credit-deposit relationship in optimizing NIM. The findings provide insights for Nepal's policymakers, banking regulators, and commercial banks to enhance profitability and financial stability.